2014
DOI: 10.1089/tmj.2013.0086
|View full text |Cite
|
Sign up to set email alerts
|

Hot Spot: Impact of July 2011 Heat Wave in Southern Italy (Apulia) on Cardiovascular Disease Assessed by Emergency Medical Service and Telemedicine Support

Abstract: Increased work burden for EMS assessed with prehospital telecardiology screening accompanies heat waves because of subjects calling for suspected acute heart disease. Prehospital screening with telecardiology support may be of help in identifying subjects who do not require hospitalization in the event of heat waves with increased calls to EMS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 83 publications
1
15
0
Order By: Relevance
“…An 8% increase in BLS demand and a 14% increase in ALS demand on days with extreme heat was recently reported in King County, Washington during the spring and summer months over a 5-year period (18). Similar studies evaluating heat waves and increased EMS use have been reported in Boston (32), Atlanta (33), and Phenix (34), Australia (35,36), Canada (37,38), Italy (39), Japan (40), and Switzerland (41). The findings from our study support and add to these studies by identifying a greater all-cause need for EMS during periods of higher temperature using granular hourly temperature data.…”
Section: Discussionsupporting
confidence: 88%
“…An 8% increase in BLS demand and a 14% increase in ALS demand on days with extreme heat was recently reported in King County, Washington during the spring and summer months over a 5-year period (18). Similar studies evaluating heat waves and increased EMS use have been reported in Boston (32), Atlanta (33), and Phenix (34), Australia (35,36), Canada (37,38), Italy (39), Japan (40), and Switzerland (41). The findings from our study support and add to these studies by identifying a greater all-cause need for EMS during periods of higher temperature using granular hourly temperature data.…”
Section: Discussionsupporting
confidence: 88%
“…Previous studies showed that occasional hype in mass media and press may negatively impact annual rates of influenza vaccination, with consequent dramatic impact on emergency service workloads supported by telemedicine [23]. Catastrophic events may also translate into peaks in emergency and telemedicine calls and stressed emergency services [24].…”
Section: Discussionmentioning
confidence: 99%
“…A related and rapidly accumulating body of research assesses the relationship between high temperature and health events other than mortality: hospital admissions and emergency department (ED) visits ( Hess et al 2014 ; reviews by Kravchenko et al 2013 ; Martiello and Giacchi 2010 ; Ye et al 2012 ), hospital admissions among patients seen in the ED ( Pillai et al 2014 ), ambulance/emergency response calls ( Alessandrini et al 2011 ; Hartz et al 2013 ; Nitschke et al 2011 ; Schaffer et al 2012 ; Williams et al 2012a , 2012b ), teleradiology calls ( Brunetti et al 2014 ), and outpatient visits ( Pudpong and Hajat 2011 ). However, only a few studies have considered more than one measure of health effects associated with heat, for a single geographic region, at the same time (e.g., Kovats et al 2004 ; Williams et al 2012a , 2012b ).…”
Section: Introductionmentioning
confidence: 99%